2015
DOI: 10.1002/pc.23674
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of poly(l‐lactic acid) composites filled with mesoporous silica

Abstract: The mechanical properties of mesoporous silica (MCM‐41) filled poly(l‐lactic acid) (PLA4032D) composites and PLA4032D/poly(ethylene glycol) (PEG) composites were investigated. It was found that the Young's modulus increased while tensile strength decreased with increasing the filler content; the V‐notched impact fracture strengths of both Izod and Charpy for the PLA4032D/PEG/MCM‐41 composites increased while they decreased slightly for the PLA4032D/MCM‐41 composites, the unnotched Charpy impact strength of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Recently, ordered mesoporous silicas, particularly MCM-41 have increasingly received enormous attention as filler owing to their highly tailorable properties such as high surface area, large pore sizes with narrow distribution and well-ordered regular framework structure [19][20][21][22]. The polymer nanocomposites prepared by MCM-41 particles shows some unusual properties mainly due to the presence of the constrained organic phase within or outside the hexagonal pores of an inorganic material at the molecular level [4,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, ordered mesoporous silicas, particularly MCM-41 have increasingly received enormous attention as filler owing to their highly tailorable properties such as high surface area, large pore sizes with narrow distribution and well-ordered regular framework structure [19][20][21][22]. The polymer nanocomposites prepared by MCM-41 particles shows some unusual properties mainly due to the presence of the constrained organic phase within or outside the hexagonal pores of an inorganic material at the molecular level [4,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…As the surface area is increased, the interfacial adhesion with EPDM matrix enhances resulting decrease in mobility of the polymer chain. The mesoporous structure also plays an important role, where the pores act as crosslinking point to improve interfacial interaction between EPDM matrix and filler [22]. The interfaces between the silica and polymer matrix could transfer stress from matrix to inorganic particles, which could improve the tensile strength [52].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polylactic acid (PLA), as a kind of the biological renewable materials, is derived from corn, starch and sugar . Because of its biocompatibility, biodegradability, easy processibility and good transparency, PLA shows profound prospects in many applications, such as automotive field, electronic field and biomedical materials . However, the use of PLA is restricted due to its inherent brittleness and inflammability .…”
Section: Introductionmentioning
confidence: 99%
“…Also the electrical properties like dielectric constant play an important role in the proper functioning of the electronic circuit board substrate, as low dielectric constant is demanded for substrates in high-frequency appliances. Wu et al [21] reported the dielectric properties of epoxy matrix filled with inorganic filler in a frequency range of 1 Hz to 1 MHz whereas Ling et al [22] studied a new class of multi filler composite for such microelectronics applications.…”
Section: Introductionmentioning
confidence: 99%